Empire, power and indigenous elites a case study of the Nehemiah memoir - Fitzpatrick-McKinley, Anne (Supplements to the Journal for the study of Judaism, 2015)
Near Eastern empires and indigenous elites : rethinking ancient empire -- Judah on the eve of Persian rule -- Persian practices in Transeuphratene : the wider context of Nehemiah's rule -- Territories and populations : dealing with diversity -- Regions closer to Yehud under Persian rule : indigenous elites in Lycia, Phoenicia, Arabia and Samaria -- Local politics in Achaemenid Yehud prior to Nehemiah -- Nehemiah and local politics : the later Achaemenid period -- Nehemiah's use of "law" in controlling his opponents -- The basis of Nehemiah's lawmaking